1993
DOI: 10.1113/jphysiol.1993.sp019538
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization of group II muscle afferents by stimuli applied in the locus coeruleus and raphe nuclei of the cat.

Abstract: SUMMARY1. Electrical stimuli applied in the locus coeruleus/subcoeruleus (LC/SC) and raphe nuclei produce a profound depression of transmission in reflex pathways from group II muscle afferents. The present experiments were performed to determine whether presynaptic inhibitory mechanisms contribute to these effects.2. Changes in the excitability of afferent terminals to electrical stimuli have been used as an indication of primary afferent depolarization (PAD) produced by conditioning stimuli applied within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 43 publications
(58 reference statements)
2
52
0
Order By: Relevance
“…There are also indications that neuronal systems mediating presynaptic inhibition are activated by the conditioning stimuli applied in the LC/SC and raphe nuclei since such stimuli produce depolarization of the terminals of group II afferents in the midlumbar segments (Riddell, Jankowska & Eide, 1993). It is not clear at present whether monoaminergic or non-monoaminergic systems are involved in these actions (see Discussion of Riddell et al 1992).…”
Section: The Site Of the Depressive Actionsmentioning
confidence: 99%
“…There are also indications that neuronal systems mediating presynaptic inhibition are activated by the conditioning stimuli applied in the LC/SC and raphe nuclei since such stimuli produce depolarization of the terminals of group II afferents in the midlumbar segments (Riddell, Jankowska & Eide, 1993). It is not clear at present whether monoaminergic or non-monoaminergic systems are involved in these actions (see Discussion of Riddell et al 1992).…”
Section: The Site Of the Depressive Actionsmentioning
confidence: 99%
“…For example, Jankowska and coworkers have demonstrated that 5-HT and raphe-spinal stimulation can exert a dierential control over primary aerent-evoked responses of dierent modalities (e.g. Riddell et al, 1993;Jankowska et al, 1997;. A third limitation to this study is that the DDH is functionally heterogeneous, yet all dorsal horn neurons were treated here as a single population.…”
Section: Limitations Of the Experimental Approachmentioning
confidence: 99%
“…There is considerable information available on the sources of PAD of cutaneous afferents (e.g. Schmidt, 1971;Baldissera, Hultborn & Illert, 1981), group I (see Baldissera et al 1981;Rudomin, 1990) and group II muscle afferents (Harrison & Jankowska, 1989;Riddell, Jankowska & Eide, 1993), interosseous and joint fibres (Jankowska, Riddell & McCrea, 1993), and C fibres (Woolf & Fitzgerald, 1982). In contrast, less is known about sources of PAD of SPud afferents.…”
Section: Observations) During Micturition In Catsmentioning
confidence: 99%